Nutritional and Functional Characteristics of Senescent Plantain Powder Mix - Doreen, Adi Dedo; Oduro, Ibok N; Tortoe, Charles (Food, Agriculture and Natural Resources - NETWORKS, 2024)
Post-harvest loss of plantain peeks at senescence. Drying senescent plantain enhances its culinary applications. This study aimed to determine the biochemical and functional properties of foam-mat dried senescent plantain samples, and their respective powdered mixes prepared for baking ofam (an Indigenous spicy cake). The nutritional benefits of foam-mat dried senescent plantain, with its high vitamin C and total carotenoid content, make it a valuable addition to dietary interventions. Foam-mat dried plantain samples and their respective powdered mixes were evaluated for their proximate composition, vitamin C, total carotenoids, amino acid contents, water and oil absorption capacities, and least gelation concentration using standard methods. The products were predominantly carbohydrates (73.3g - 80.4g/100g) with low moisture contents (9.19 - 20.68 g/100g). Vitamin C and total carotenoids ranged from 17.42 mg/100g to 33.99 mg/100g and 3.4 to 7.2 µg/g respectively. The samples had appreciable amounts of calcium (78.90 - 175.18 mg/100g), magnesium (112.13 - 113/79 mg/100g), potassium (95.76 - 77.09 mg/100g), iron (17.65 - 12.76 mg/100g) and zinc (10.94 - 15.82 mg/100 g). The most abundant amino acids were phenylalanine, histidine, methionine and aspartic acid. Sample SPPFSCF exhibited the best gelation capacity (22 g/100 mL). The water absorption capacities of the samples were influenced by the flour type used. However, the variations in the oil absorption capacities of the powdered mixes were statistically insignificant. EAPFRCF absorbed the least oil (0.84 g/g) while SPPFSCF absorbed the most (0.94 g/g). Foam-mat dried senescent plantain and their powdered mixes have the potential for utilization in nutritional interventions. Its low moisture content will support a longer shelf-life than the fresh overripe plantain.